(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
In Latvia the total renewable energy resource volume has not been fully evaluated. Reed exploitation for energy output has not been developed on a large scale. One of the factors for this is the lack of information about to reed resource spread and characteristics. Therefore, there arises the need for a united inventory system – the formation of a reed cadaster. The study contains information on basic principles of reed cadastre creation and research methodologies. The reed cadaster is a list of the reed researches which contains information about the reed areas in Latvia, the volume and locations, the legal status, possibilities for exploitation, as well as the biomass qualities, in each specific water reservoir. For each water reservoir, which is included in the reed cadaster, a certificate and chart have been produced. Information about the reed locations in each specific lake have been shown on the cadaster chart; the boundaries of the water reservoir, the boundaries of the reed plants and areas, the natural habitat protected area boundaries, the district boundaries, as well as the access roads. The data for reed characteristics and accessible volumes is compiled in the water reservoir cadaster passport. Development for reed exploitation in the conditions of Latvia is dependent on the location, accessible volumes and existing infrastructure. Reeds are a long term renewable energy resource, with the spread of reeds increasing every year.